Role of the Annexin A protein family in liver diseases: insights and therapeutic opportunities - Mingyang Feng; Yong He; Hui Wang (Frontiers in Pharmacology)
The Annexin (ANXA) protein family, which is ubiquitously expressed across various tissues, encodes versatile calcium (Ca2+)- and phospholipid-binding proteins that play crucial roles in modulating inflammation and cell signaling pathways. This family significantly influences several essential cellular processes, including cell adhesion, proliferation, migration, differentiation, and apoptosis. ANXAs are integral to physiological regulation and the pathological states associated with liver diseases. Dysregulated expression of ANXAs has been linked to a spectrum of liver conditions, including metabolic dysfunction, hepatocyte damage, fibrosis, and tumor formation. In this review, we outline recent advancements in understanding the roles of ANXAs in liver diseases. Further investigation into the roles of ANXAs in the liver could enhance our understanding of the mechanisms underlying liver diseases and may identify biomarkers and therapeutic targets for liver diseases in the future.